2017
DOI: 10.1002/em.22145
|View full text |Cite
|
Sign up to set email alerts
|

A regenerative erythropoietic response does not increase the frequency of Pig‐a mutant reticulocytes and erythrocytes in Sprague‐Dawley rats

Abstract: The in vivo rodent Pig-a mutation assay is a sensitive test to identify exposure to mutagenic substances, and has been proposed as an assay for the identification of impurities for pharmaceuticals. Red blood cells (RBCs) and reticulocytes (RETs) are analyzed by flow cytometry after exposure to potentially mutagenic chemicals for cells deficient in the cell surface anchored protein CD59, representing mutation in the X-linked Pig-a gene. The full potential of the assay as well as its limitations are currently be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The data demonstrate that the Pig‐a endpoint was negative in peripheral blood RETs and RBCs from acetaminophen‐(≤1,000 mg·kg −1 ·day −1 ) treated rats dosed up to 29 days and that temporarily marked reduction in the %RET did not trigger a positive response in the Pig‐a assay. The changes in the hematopoiesis did not appear to cause a positive finding in the Pig‐a endpoint which was also demonstrated by the work of Kenyon et al ., 2015 and Nicolette et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The data demonstrate that the Pig‐a endpoint was negative in peripheral blood RETs and RBCs from acetaminophen‐(≤1,000 mg·kg −1 ·day −1 ) treated rats dosed up to 29 days and that temporarily marked reduction in the %RET did not trigger a positive response in the Pig‐a assay. The changes in the hematopoiesis did not appear to cause a positive finding in the Pig‐a endpoint which was also demonstrated by the work of Kenyon et al ., 2015 and Nicolette et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation and increase in cell division associated with IBD might be responsible for the slight elevation in PIG‐A MF. But some rodent Pig‐a studies also indicated that the regenerative erythropoietic response does not lead to increase Pig‐a MFs (Kenyon et al ; Nicolette et al ). Thus, we interpret the results of PIG‐A assay in our study only as a weak positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, when blood is collected several days or more after discontinuing treatment, it can manifest as elevated %RET frequencies due to stress erythropoiesis. (Note that Nicolette et al ., 2018 demonstrated that regenerative erythropoietic response does not increase the frequency of MUT RET/RBC in rats.) Test substance‐induced hemolysis is another situation that can manifest as elevated frequencies of reticulocytes and represents evidence of systemic exposure (Kenyon et al ., 2015).…”
Section: Systemic Exposurementioning
confidence: 96%